CHALLENGING THE NEW CURSE OF BIGNESS. - RAHMAN, K. SABEEL (American Prospect)
The article discusses the excessive economic and political power of big finance in the U.S. Topics being focused here include the progressive legacy and its new application, antitrust, and public utility regulation. Also being discussed are public options, public utility regulation and the internet, and the problem of finance.